2014
DOI: 10.1002/hed.23780
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of integrin β6 as a tumor recurrence factor in follicular thyroid carcinoma

Abstract: Integrin β6 expression correlated significantly with MMP-9 expression, and may be a valuable recurrence indicator for follicular thyroid carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Several studies in cell models and primary tumors demonstrated the biological role and potential clinical impact of integrins in thyroid tumors. Expression of integrin subunit β4 correlates with lymph node metastasis in papillary carcinomas, and integrin subunit β6 significantly correlates with recurrence of follicular thyroid carcinoma (FTC) [18,19]. Inhibition of α5β1 binding to ECM prevents attachment of FTC cell lines to the bone matrix [20], while RET-induced cell adhesion and migration of papillary thyroid carcinoma (PTC) cell lines required β1 and β3 integrins in vitro and in a mouse tumor xenograft model [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in cell models and primary tumors demonstrated the biological role and potential clinical impact of integrins in thyroid tumors. Expression of integrin subunit β4 correlates with lymph node metastasis in papillary carcinomas, and integrin subunit β6 significantly correlates with recurrence of follicular thyroid carcinoma (FTC) [18,19]. Inhibition of α5β1 binding to ECM prevents attachment of FTC cell lines to the bone matrix [20], while RET-induced cell adhesion and migration of papillary thyroid carcinoma (PTC) cell lines required β1 and β3 integrins in vitro and in a mouse tumor xenograft model [21].…”
Section: Introductionmentioning
confidence: 99%